(untitled) (Scientific journal of the Fergana State University, 2025)
In this work, it is presented that in saline soils of different properties, the composition and quantity, as well as the sum of absorbed bases, vary differently depending on the state, i.e., natural saline soils and secondary saline soils of different ages possess the properties of calcium and magnesium saturation. From natural saline soils to secondary ones, there is an increase in absorbed calcium, a decrease in the content of magnesium and sodium.